Comparative experimental investigation of natural fibers reinforced light weight concrete as thermally efficient building materials. (September 2020) - Asim, Muhammad; Uddin, Ghulam Moeen; Jamshaid, Hafsa; Raza, Ali; Rehman Tahir, Zia ul; Hussain, Uzair; Satti, Aamir Naseem; Hayat, Nasir; Arafat, Syed Muhammad
Abstract: The building insulation is one of the needed element or component in building construction; it protects the construction against heat leakage for saving energy. The current research work aims to utilize natural fibers in concrete and develop such type of environmentally friendly material that has better thermal insulation properties. Thermal conductivity test, scanning electronic microscope tomography (SEM) and microscopic images for interfacial bonding of fibers with concrete were performed for plain concrete and natural fibres light weight reinforced concrete (RC) samples. Thermo-gravimetric analysis (TGA) was performed to check the thermal stability of natural fibres RC. The compressive strength was also measured to investigate the mechanical cost at which thermal insulation is achieved. Thermal conductivity results showed that by increasing the percentage of natural fibres (Jute, Coconut, Sugar cane, Sisal, Basalt) in concrete the thermal insulation characteristics increased while compressive strength decreased. TGA indicated that Jute, Sugarcane and Basalt fibres RC have better thermal stability as compared with plain concrete up to 50 °C which is suitable for South Asian countries climate but Sisal and Coconut fibres reinforced samples have comparatively a bit lower thermal stability. However, at 2.5% mixing of coconut and jute we were able to achieve improvement in both compressive strength and thermal insulation.